2020
DOI: 10.1167/iovs.61.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D3 (α-1, 25(OH) 2D3) Protects Retinal Pigment Epithelium From Hyperoxic Insults

Abstract: Citation: Murugeswari P, Firoz A, Murali S, et al. Vitamin-D3 (α-1, 25(OH) 2D3) protects retinal pigment epithelium from hyperoxic insults. Invest Ophthalmol Vis Sci. 2020;61(2):4. https://doi.org/10.1167/iovs.61.2.4 PURPOSE.Oxidative stress affects the retinal pigment epithelium (RPE) leading to development of vascular eye diseases. Cholecalciferol (VIT-D) is a known modulator of oxidative stress and angiogenesis. This in vitro study was carried out to evaluate the protective role of VIT-D on RPE cells incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Additionally, our results demonstrated that application of N and ND to the media counteracted these morphological changes. Earlier investigations demonstrated that vitamin D restored damaged tight junctions and increased ZO-1 protein levels in ARPE-19 cells under oxidative stress conditions [ 36 , 46 ], which suggests its role in blood–retinal barrier integrity through intercellular adherent junctions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, our results demonstrated that application of N and ND to the media counteracted these morphological changes. Earlier investigations demonstrated that vitamin D restored damaged tight junctions and increased ZO-1 protein levels in ARPE-19 cells under oxidative stress conditions [ 36 , 46 ], which suggests its role in blood–retinal barrier integrity through intercellular adherent junctions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results demonstrate significant reduction in cell proliferation after addition of H 2 O 2 in both cell lines, characterized by subsequent recovery following application of either N or ND to the media, with ND presenting a more potent effect than N in HREC cells. Earlier studies have effectively described the vital role of oxidative stress by H 2 O 2 in inhibiting cell proliferation in various cells [ 62 ], including RPE in the retina [ 35 , 46 , 63 , 64 ]. The exact mechanisms have not been identified, however, recent studies have revealed the interference of H 2 O 2 in numerous intracellular signaling pathways in retinal epithelial cells, such as the epidermal growth factor receptor/AKT and Notch signaling pathways [ 46 , 64 ], including the regulation of autophagy [ 65 ], kinases, and pro-apoptotic proteins such as caspases [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hyperoxic insult and apoptosis have been examined in the presence of various vitamins as a rescuing factor [ 100 ]. Kaempferol protects retinal pigment epithelium cells from hydrogen peroxide-induced inflammation and apoptosis by activating SIRT1 and inhibiting PARP1, which opens up a significant gateway for more experiments and further insights [ 101 ].…”
Section: Kaempferol: a Potential Multifunctional Flavonoid Against Co...mentioning
confidence: 99%
“…3,4 Accordingly, as they are important nonenzymatic anti-oxidative agents in the retina, vitamins and carotenoids were hypothesized to protect the retina from oxidative damage, which suggests that these nutrients play an important role in preventing the process of vision impairment. 5,6 In particular, lutein and its structural isomer, zeaxanthin, which are concentrated in the macula, have also been suggested to play a role in protecting the macular region by acting as a blue light filter, thereby decreasing photochemical light damage. 7 To date, conflicting results have been reported on the association between the intakes of antioxidants, such as lutein, vitamin C and β-carotene, and AMD, with some demonstrating a possible inverse association have been reported [8][9][10][11][12][13] , whereas other studies showed no clear association.…”
Section: Introductionmentioning
confidence: 99%